A GENDER WELFARE IMPACT OF THE ECOWAS COMMON EXTERNAL TARIFFS ON HOUSEHOLDS IN TOGO - Kwami Ossadzifo Wonyra; Muriel Eyram Silo Ametoglo; Ping Guo (International Journal of Food and Agricultural Economics, 2017)
This paper evaluates the welfare outcomes of implementing the ECOWAS common external tariff in Togo, with a specific focus on gender issue. Using the survey data QUIBB 2015, we perform an induced price analysis and a non-parametric regression. We find that the share of household expenditure allocated for food declines as the income level increases, in both urban and rural areas and for both male- and female-headed households. The results also denote that ECOWAS-CET has reduced the welfare of consumer households in Togo, especially for self-employed farmers. As supported by the theory, consumer households living closer to the port city observe a smaller loss in the welfare. Our analysis shows that households in Lomé (where the distance from the port city is zero) experienced the lowest loss in the welfare while households in the Savanes region (at 617.7 kilometers from the port) have the biggest loss score. In Togo, government social transfer is pro-poor because it leaves the poor better off, but it benefits more to male-headed households.